Guidelines for Opioid Prescribing in Children and Adolescents After Surgery: An Expert Panel Opinion - Kelley-Quon, Lorraine I; Kirkpatrick, Matthew G; Ricca, Robert L; Baird, Robert; Harbaugh, Calista M; Brady, Ashley; Garrett, Paula; Wills, Hale; Argo, Jonathan; Diefenbach, Karen A; Henry, Marion C W; Sola, Juan E; et al. (JAMA surgery, 2021)
Opioids are frequently prescribed to children and adolescents after surgery. Prescription opioid misuse is associated with high-risk behavior in youth. Evidence-based guidelines for opioid prescribing practices in children are lacking. To assemble a multidisciplinary team of health care experts and leaders in opioid stewardship, review current literature regarding opioid use and risks unique to pediatric populations, and develop a broad framework for evidence-based opioid prescribing guidelines for children who require surgery. Reviews of relevant literature were performed including all English-language articles published from January 1, 1988, to February 28, 2019, found via searches of the PubMed (MEDLINE), CINAHL, Embase, and Cochrane databases. Pediatric was defined as children younger than 18 years. Animal and experimental studies, case reports, review articles, and editorials were excluded. Selected articles were graded using tools from the Oxford Centre for Evidence-based Medicine 2011 levels of evidence. The Appraisal of Guidelines for Research & Evaluation (AGREE) II instrument was applied throughout guideline creation. Consensus was determined using a modified Delphi technique. Overall, 14 574 articles were screened for inclusion, with 217 unique articles included for qualitative synthesis. Twenty guideline statements were generated from a 2-day in-person meeting and subsequently reviewed, edited, and endorsed externally by pediatric surgical specialists, the American Pediatric Surgery Association Board of Governors, the American Academy of Pediatrics Section on Surgery Executive Committee, and the American College of Surgeons Board of Regents. Review of the literature and guideline statements underscored 3 primary themes: (1) health care professionals caring for children who require surgery must recognize the risks of opioid misuse associated with prescription opioids, (2) nonopioid analgesic use should be optimized in the perioperative period, and (3) patient and family education regarding perioperative pain management and safe opioid use practices must occur both before and after surgery. These are the first opioid-prescribing guidelines to address the unique needs of children who require surgery. Health care professionals caring for children and adolescents in the perioperative period should optimize pain management and minimize risks associated with opioid use by engaging patients and families in opioid stewardship efforts.